(untitled) (Web of Teachers: Inderscience Research, 2024)
In our country, special attention is paid to the content of education, national educational programs are put into practice, pedagogical technologies and information communication tools are used to increase the effectiveness of the educational process based on pedagogical technologies. It is important to correctly choose and use the methods, tools and forms of pedagogical technologies in order to expand the students’ worldview, wide and easy assimilation of knowledge in the education of primary school students. Many methods of pedagogical technologies are used in the organization of reading classes.